ISO 9001 Quality Management Systems: Critical Analysis of Literature Review - Saraiva, Margarida (2018)
Purpose and Methodology/Approach: This paper follows a previous one focused on a bibliographic review of motivations, benefits and difficulties in implementing quality management systems (QMS) based on ISO 9001 standard (Saraiva et al, 2017). Controversial, conflicting and even contradictory, and/or non-consensual findings in same or different countries have suggested other dimensions were lacking. So, a further and critical analysis was deepened in order to identify possible flaws in dimensions of analysis and in methodological issues, which is the scope of this paper. Findings: Many research works were based on perceptions/opinions (eg. motivations, benefits, difficulties) and tangible results were missing, being conclusions built only on qualitative data. Quantitative data were not used to objectivize and validated qualitative findings. Physical or economic indicators rarely were presented. Researchers may not have asked for quantitative data or even ignore these aspects of organizational reality, or the organizations also do not have this type of data. It is hard to corroborate statements (from company’s managers) or findings (from researchers) without other objective evidences (examples are: motivations influence the QMS performance; cost reduction is a benefit; the biggest difficulties in implementation/certification of QMS are the excessive and complex (bureaucratic) documentation, the weak commitment to quality by management and staff, the high cost/scarce resources and the time spent with the additional tasks for the implementation process; organizations operating an ISO 9001 QMS show a better performance). Another matters such as the relative size of the certification phenomenon in each country or region and their economic and social development were generally unknown or were not taken into account. These contextual factors can distort findings. The scientific affiliation of researchers (eg. Industrial engineering, Management, Sociology, Organizational psychology) may also have implications for the research perspective and aspects that are privileged in analysis and conclusions. Research Limitation/implication: Additionally, other methodological issues can also be related to data collection instruments (eg. questionnaires to collect perceptions/opinions) are not the most appropriate for achieving some desired information or data processing does not validate conclusions. Thus, we will take into account in our future research these limitations we have identified in this one and strongly recommend to other researchers our conclusions. Originality/Value of paper:These reflections and findings suggest further and deeper work for research in QMS and other related topics, looking for those dimensions already identified as missing, and/or considering more dimensions, bearing in mind concerns that quality movement is losing popularity, because it does not appear to managers consistently with quantitative data proving contributions of quality to increase productivity and competitiveness. Finally, we raise methodological questions about research on these topics, and other dimensions of analysis are recommended.